NURSING TURNOVER- AN OVERVIEW AND UPDATES FROM KINGDOM OF SAUDI ARABIA - Bdoor Badi Alosaimi, Mishal Mubarak Faleh Al-Dosari, Hammad Mahammed Hammad Aldosari, ⁠Abdulaziz Obaid Saad Al Doseri, Khulud Raja Nazal Alshammari, ,; Tarrah Almajdi, Fatmah Saleh Alshomemeri,⁠ Saleh Salem Aljeri,⁠ Amal Gaber Alrowily, ⁠Maha Ghadeef Alanazi,⁠ Rahma Mohammed Alhawsawi, Hind Yosef Mohammad Aldosari, ,; Abeer Hussain Aldossari,‏ Tariq Abdullah Alotaibi, Lajwa Talaq Alotibi, Abdulrahman Saeed Alqahtani, (Chelonian Research Foundation, 2022)
The complicated topic of nurse turnover in healthcare systems is impacted by a number of organizational, personal, and environmental factors. This paper offers a summary of the large body of research on nurse turnover, concentrating on important factors and how they affect retention tactics. Workload, management style, opportunity for advancement, and work schedules are a few examples of organizational elements that have a big impact on how happy and retained nurses are in their jobs. There is a significant correlation between lower turnover rates and leadership that values employee contributions, empowerment, and career growth chances. Furthermore, it has been demonstrated that interventions like career progression programs and flexible schedules increase nurse retention. Individual characteristics including age, experience, and obligations to their families can influence a nurse's decision to remain in or quit their position. Compared to their younger counterparts, older, more experienced nurses typically show better levels of job satisfaction and lower turnover rates. Workplace modifications may be necessary to meet the demands of nurses due to family responsibilities, such as taking care of elderly parents or children. Although significant advancements have been achieved in comprehending the components that influence nurse turnover, additional investigation is required to examine the interaction between organizational and individual elements and their combined influence on turnover rates. Further research is also necessary to determine how higher nursing education affects turnover rates and how important it is to fund nursing programs in order to lessen dependency on foreign expertise. In order to guarantee the retention of qualified and committed nursing personnel and, ultimately, support the provision of high-quality patient care, addressing nurse turnover necessitates a comprehensive strategy that considers both organizational and individual aspects.